Answer:
(-2, 1)
Explanation:
Given:
2x+8y=4...(1)
6x-y=-13...(2)
You would want to have an x or a y value that equals the same in both equations. In this case, we can multiply equation 1 by 3 so that both x's in each equation equal 6x.
(2x+8y=4) x 3...(1)
6x-y=-13...(2)
becomes...
6x+24y=12...(3)
6x-y=-13...(4)
As you can see here, both x's in this equation are equal.
Now we will be combining these equations together. Take the equal x values and make sure they will equal 0. You do that by either subtracting the entire equation or adding it. In this problem, we will be subtracting it because 6x-6x=0
(6x+24y=12) - (6x-y=-13) = 25y =25
Now that we can solve for y separately, 25y=25 y=1
To solve for x, just substitute y into one of the original equations (equations 1 or 2). For this problem, I'll use equation 1.
6x-y=-13
6x-1=-13
6x=-12
x=-2
(This is what I got for my answer and here is the explanation. I apologize if my answer is incorrect. If someone notices a mistake in my answer, please correct me, thank you and have a nice day!)